2012
DOI: 10.1530/erc-12-0286
|View full text |Cite
|
Sign up to set email alerts
|

Release of macrophage migration inhibitory factor by neuroendocrine-differentiated LNCaP cells sustains the proliferation and survival of prostate cancer cells

Abstract: The acquisition of neuroendocrine (NE) characteristics by prostate cancer (PCa) cells is closely related to tumour progression and hormone resistance. The mechanisms by which NE cells influence PCa growth and progression are not fully understood. Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine involved in oncogenic processes, and MIF serum levels correlate with aggressiveness of PCa. Here, we investigated the regulation and the functional consequences of MIF expression during NE tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…The belief that an immune response opposes NETs is also substantiated by the frequent finding of lymphocyte infiltration of NETs, as assessed by immunohistochemistry for CD3 (a general T lymphocyte marker), CD4, CD8 and CD56 [22,23,24,25]. Other studies have also been conducted on the immune system [26,27,28]. Immunotherapies are now being used clinically to inhibit several immune cell subsets that promote tumor development [29].…”
Section: Discussionmentioning
confidence: 99%
“…The belief that an immune response opposes NETs is also substantiated by the frequent finding of lymphocyte infiltration of NETs, as assessed by immunohistochemistry for CD3 (a general T lymphocyte marker), CD4, CD8 and CD56 [22,23,24,25]. Other studies have also been conducted on the immune system [26,27,28]. Immunotherapies are now being used clinically to inhibit several immune cell subsets that promote tumor development [29].…”
Section: Discussionmentioning
confidence: 99%
“…As for macrophage migration inhibitory factor (MIF), it is a pro-inflammatory cytokine involved in prostate carcinogenesis. In vitro studies reported that NE differentiation of LNCaP cells is associated with markedly increased MIF release, which promotes the proliferation of PCa cells through the stimulation of the AKT and ERK1/2 signaling pathways [20].…”
Section: The Origin Of Ne Cells and Their Contribution To Prostate Camentioning
confidence: 99%
“…Results from a study comparing pNET patients and healthy unrelated controls indicated an association between the high-expression C/T-511 IL1b (IL1B) genotype and susceptibility to pNETs (Cigrovski Berkovic et al 2012). Interestingly, macrophage migration inhibitory factor (MIF) has been recently linked to neuroendocrine differentiation in prostate cancer (Tawadros et al 2013). Immunotherapies are now being used clinically to inhibit several immune cell subsets that promote tumour development (Coussens et al 2013).…”
Section: Tumour-promoting Inflammationmentioning
confidence: 99%